A Educação Não-Formal a partir dos relatórios da UNESCO - Bendrath, Eduard Angelo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study is related to the line of research: Public Policy, School Organization and Teachers Training, of the Education Post-Graduate Program - Faculty of Sciences and Technology, Sao Paulo State University. With the expansion of educational movements parallel to the formal education system, educational activities focusing on the processes of human and economic development have become important tools for solving local problems, leading to new guidelines in the construction of arrays of non-formal education around the world. Such assumptions are in accordance with international political conceptions currently prevailing, in an attempt to match economic growth and social development with reference to social and human capital accumulation models. The social capital arises as an appreciation mechanism of collective action towards the establishment of trust and reciprocity relations, while the human capital favors individual advances opportunities with reference to new requirements of economic and social demands, both having non-formal education as a central point for their initiatives. Thus, this research aimed of the analysis of UNESCO documents in 31 countries verifying the relationship between non-formal education policies and economic and social development principles with the basis of social and human capital, as well as the direct interest of local governments and the involved international organizations...

O presente estudo está vinculado à linha de pesquisa: Políticas Públicas, Organização Escolar e Formação de Professores, do Programa de Pós-graduação em Educação da Faculdade de Ciências e Tecnologia da Universidade Estadual Paulista. Com a expansão de movimentos educativos paralelos ao sistema formal de ensino, as ações educacionais com foco nos processos de desenvolvimento humano e econômico tornaram-se importantes ferramentas para a resolução de problemas locais, o que encaminhou novas diretrizes nas construções de matrizes de educação não-formal ao redor do mundo. Tais pressupostos alinham-se às concepções políticas internacionais atualmente vigentes, na tentativa de adequar o crescimento econômico ao desenvolvimento social tomando como referência os modelos de acumulação do capital social e capital humano. O capital social surge como mecanismo de valorização da ação coletiva em prol do estabelecimento de laços de confiança e reciprocidade, ao mesmo tempo em que o capital humano favorece possibilidades de avanços individuais frente a novas demandas econômicas e sociais, ambos tendo a educação nãoformal como ponto de convergência para suas iniciativas. Dessa forma esse estudo tomou como parâmetro a análise de documentos da UNESCO em 31 países cujo objetivo foi verificar a relação estabelecida entre as políticas de educação não-formal e os princípios do desenvolvimento econômico e social com aporte às bases do capital social e humano...
Keywords: Unesco; Educação; Politicas publicas; Educação não-formal; Education